End times: elites, counter-elites, and the path of political disintegration - Turchin, Peter (Allen Lane, an imprint of Penguin Books, 2023)
"From the pioneering co-founder of cliodynamics, the ground-breaking new interdisciplinary science of history, a brilliant big-picture explanation for America's civil strife and its possible endgames Peter Turchin, one of the most interesting social scientists of our age by any measure, has infused the study of history with approaches and insights from other fields for over a quarter century. The Wealth Pump is the culmination of his work to understand what causes political communities to cohere and what causes them to fall apart, as applied to the current turmoil within the United States. Back in 2010, Nature magazine asked Turchin, along with other leading scientists, to provide a ten-year forecast. Based on his models, Turchin predicted that America was in a spiral of social disintegration that would lead to a breakdown in the political order ca 2020. As the years passed, and his prediction proved accurate in more and more respects, attention around his work grew. The Wealth Pump distills his framework, its empirical justification, and its highly relevant findings, into an accessible, thought-provoking book that puts the American story into broad historical context. The lessons of world history are clear, Turchin argues: when the equilibrium between ruling elites and the majority tips too far in favor of elites, political instability is all but inevitable. Before the industrial era, the imbalance between labor and capital, signaled by rising economic inequality, was usually caused by excessive population growth. For the past 250 or so years, it has been laissez-faire government, technological innovation, globalization, and immigration that have tended to disrupt the balance. Whatever the cause, when income inequality surges, the common people suffer, and prosperity flows disproportionately into the hands of the elites. This vicious cycle is the "wealth pump" -the mechanism that causes both the relative impoverishment of most people and the increasingly desperate competition among elites. And since the number of positions of real social power remains relatively fixed, the overproduction of elites inevitably leads to frustrated elite aspirants, who harness popular resentment to turn against the established order. History shows that when the elite is riven by too many claimants, when counter-elites are powerful enough to lead effective populist uprisings, then the death knell of the established order is nigh. In America, the wealth pump has been operating full blast for two generations. In historical terms, our current cycle of elite overproduction and popular immiseration is far along the path to violent political rupture. Time will tell whether Peter Turchin's warning is heeded"